PENGARUH SUHU DAN LAMA THAWING DI DATARAN TINGGI TERHADAP KUALITAS SEMEN BEKU SAPI BRAHMAN - Sherly Puspa Ningrum; Madi Hartono; Purnama Edy Santosa (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
The aim of this research was to determine the lest temperature and durations of thawing athigh altitudes in frozen semen of Brahman bull. This research conducted in 8-27 March 2014. Thisresearch was conducted using a completely randomized design (CRD) with 3x3 factorial. The firstfactorial is temperature (34oC, 37oC, and 40oC) and second factorial is thawing durations with 3replications. Variables were deserved in this researchs the percentage of alive sperm and spermmotility. Research data was analyzed by Anova and Duncan test at 5%.The result showed that the temperatures and thawing durations influence the quality ofBrahman bull frozen semen, but has no interaction between them. Of this this research, the bestquality of spermatozoa obtained at 40oC and the 20 second duration of thawing has the highest qualityaverage among the other treatments. Motility of spermatozoa at 40oC is 33,89% and thawing durationat 20 second is 35,56%, the percentage of alive sperm at 40oC is 37,04% and the duration of thawingat 20 second is 35,43%.